2007
DOI: 10.1002/ajmg.c.30115
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis using cell‐free nucleic acids in maternal body fluids: A decade of progress

Abstract: The ability to detect cell-free fetal nucleic acids in pregnant women has greatly evolved over the past decade. Dozens of papers have explored the biology, kinetics, and clinical significance of both cell-free fetal DNA and mRNA in the maternal circulation. As a result, our overall understanding of fetal nucleic acid trafficking has expanded. To date, two applications, gender determination and fetal RhD status, have translated into clinical medicine. However, with advanced molecular techniques such as mass spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
1
6

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 141 publications
1
43
1
6
Order By: Relevance
“…A recent review of large-scale studies reporting on the non-invasive determination of foetal RHD status by the real-time PCR analysis of cell-free DNA indicated that accuracies between 95 and 99% could be attained [14]. As such, our data yielding an overall accuracy of 96.1% concur favourably with those obtained by real-time PCR.…”
Section: Discussionsupporting
confidence: 79%
“…A recent review of large-scale studies reporting on the non-invasive determination of foetal RHD status by the real-time PCR analysis of cell-free DNA indicated that accuracies between 95 and 99% could be attained [14]. As such, our data yielding an overall accuracy of 96.1% concur favourably with those obtained by real-time PCR.…”
Section: Discussionsupporting
confidence: 79%
“…The overwhelming majority of the literature examining fetal nucleic acid trafficking cites the placenta as the major source of fetal transcripts and utilizes plasma for their detection (21). Although some of the gene transcripts identified in this whole blood analysis were expressed in placental tissue, including placental-specific 1 (PLAC1), we did not identify other previously documented placental transcripts (PL, CRH, or hCGB) in maternal whole blood.…”
Section: Figurecontrasting
confidence: 59%
“…37 Therefore, quantification of fetal cfDNA concentrations in maternal plasma has potential for monitoring pregnancy associated-disorders, including preeclampsia. Initial studies reported a five-fold increase in plasma fetal cfDNA concentrations in women with preeclampsia (mean gestational age ͓MGA͔ 32 weeks) compared to control pregnant women.…”
Section: Discussionmentioning
confidence: 99%